2017
DOI: 10.3390/jfmk2010006
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics of Prehensility in Pushing and Pulling Motions: An Anatomical and Biomechanical Overview

Abstract: Abstract:The hand represents one of the most remarkable expressions of humanization of the anterior limb. The anterior limb, at first ambulatory, underwent continuous evolution acquiring innumerable new functions. In the course of human evolution the hand has undergone continual structural and functional adaptations, characterized, among others, by enrichment of peripheral innervation and further development of the thumb. This development was accompanied by important changes in the brain and the relocation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The evidence already suggested that the individual finger movement control was distributed widely in the human primary motor cortex hand area [42] and produced by the activity of several muscles [43]. Herein, a more insightful study from Szychlinska et al [44] is recommendable owing to the perspective of hand anatomy and biomechanics, helping to understand the neurobiological mechanisms underlying the differentiation among fingers.…”
Section: Discussionmentioning
confidence: 97%
“…The evidence already suggested that the individual finger movement control was distributed widely in the human primary motor cortex hand area [42] and produced by the activity of several muscles [43]. Herein, a more insightful study from Szychlinska et al [44] is recommendable owing to the perspective of hand anatomy and biomechanics, helping to understand the neurobiological mechanisms underlying the differentiation among fingers.…”
Section: Discussionmentioning
confidence: 97%